LMNA Determines Nuclear Morphology During Syncytialization of Human Trophoblast Stem Cells - Wang, Yiming; Wu, Hao; Jiang, Xiangxiang; Jia, Lei; Wang, Meijiao; Rong, Yin; Chen, Shuo; Wang, Yue; Xiao, Zhenyu; Liang, Xiaoyan; Wang, Hongmei (Frontiers in Cell and Developmental Biology, 2022)
Upon implantation, the trophectoderm differentiates into the multi-nucleated primitive syncytiotrophoblast (pSTB) through a process called primary syncytialization to facilitate maternal-fetal interactions and to establish a pregnancy. However, ethical issues and limited access to human embryos around the time of embryo implantation hinder the investigation of the detailed molecular mechanisms underpinning this event in humans. Here we established human trophoblast stem cells (hTSCs) from human blastocysts. We characterized nuclear enlargement in STB differentiated from hTSCs, which recapitulate morphological nuclear features of pSTB in human embryos. Specifically, we revealed that CRISPR/Cas9-mediated LMNA disruption perturbated nuclear volume during hTSCs syncytialization. Overall, our results not only provide an interesting insight into mechanisms underlying nuclear enlargement during primary syncytialization but highlight the hTSCs as an indispensable model in understanding human trophoblast differentiation during implantation.